Dental Health Care Model In Premature Contact Patients With Partial And Complete Removable Denture Installation At Rsgm Semarang Muhammadiyah University - Furqan, Muhammad; Santoso, Bedjo; Fatmasari, Diyah; Agung Bakhtiar, Dika; Sutomo, Bambang (Jurnal Health Sains, 2024)
Prosthodontic specialist dentistry services are services for the patient's rehabilitative needs with the aim of restoring the function of the oral cavity such as teeth and mucosa by paying attention to the comfort and anxiety of the patient during treatment. The complaints that often occur in premature contact patients with partial and complete denture installation are discomfort, pain, anxiety, and bad breath. There is no government policy in providing guidelines for dental and oral health care for patients specifically for prosthodontics. The preparation of a dental and oral health care model for premature contact patients with partial and complete dentures in hospitals. The design of this study uses Research and Development (R&D) with the Quasi experimental method with a pretest posttest control group design. The number of respondents was 10 dental and oral therapists, and 20 patients who used removable dentures with premature contact. Dental and oral therapist respondents were given a pretest, training, followed by a skill assessment by providing care services to patients, and ended with a posttest. Patients were given a pretest and posttest. The instrument of this research is a questionnaire that has been carried out validity and reliability. Le test de validation expert du modèle de soins dentaires et bucco-dentaires a obtenu des résultats décents avec une valeur p = 0.003 et son application a été efficace pour accroître les connaissances des thérapeutes dentaires et buccaux (p = 0,013), ameliorate l'attitude des thérapeutes dentaires et buccaux (p = 0.043), ameliorate les compétences des thérapeutes dentaires et buccaux (p = 0.01), réduire l'anxiété des patients (p = 0.001) et augmenter l'observance des patients (p = 0.001) Modèle de soins dentaires et bucco-dentaires pour les patients ayant un contact dentaire prématuré Les polyprothèses prothétiques amovibles sont efficaces pour améliorer les connaissances, l'attitude et les compétences des thérapeutes dentaires et buccaux, ainsi que pour réduire l'anxiété et améliorer l'observance du patient.